Transportation of Patients in Critical Condition Across an International Border, What is the Impact on Their Odds of Full Recovery and Survival? - Case Study at the U.S.-Mexico Border Region. Issue 1 (1st January 2022) - Salgado, David; Martin, Peter T.; Mudgal, Abhisek; Aldrete, Rafael M.; Samant, Swapnil S.; Rodriguez, Gustavo J.
ABSTRACT: This paper examines the impact of Patient Transport Time (PTT) on the transportation of critical patients in border regions when emergency medical care across an international border is required. Ambulances transport patients across the Mexico-U.S. border through Land Ports of Entry (LPOEs). The goal of this paper is to determine if PTT required to transport patients in critical condition from Mexico to the U.S. across the international border impacts their odds of full recovery and survival. The paper uses El Paso, U.S.-Ciudad Juarez, Mexico binational region as a case study. In this region, patients are transported across the border via Bridge of the Americas (BOTA) Non-commercial LPOE. Currently, there are no formal procedures to expedite ambulance cross-border operations at this LPOE. This paper concludes that PTT significantly impacts odds of full recovery and survival of patients in critical condition transported across the border. Results show that these patients will face high-risk situations, this is a significant reduction of their odds of survival, when departure time is located from 7 am to 9 am, and from noon to 8 pm. Under these circumstances, the transportation of the patient to the closest hospital in Ciudad Juarez would be safest option.